PROPTECH (PROPERTY TECHNOLOGY) BUSINESS OPERATIONAL PLANNING - Tjie Tjung; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro; Muhammad Dafi Iskandar (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
A systematic approach to establishing a technology-based property (Proptech) business in Indonesia is an urgent need in the digital era. This research is motivated by the complexity of regulations, operations, and technology faced in establishing and managing a Proptech business. The main problems identified are how to build a strong legal and administrative foundation, integrate technology effectively, and ensure efficient operations to meet market needs. This research aims to develop a Proptech operating model that covers all strategic aspects, from legality, property management, to the application of digital technology in customer service. This study highlights the importance of automation, quality management, and risk management as the keys to the success of Proptech businesses in Indonesia. The results of the research are expected to contribute to the development of integrated Proptech business policies and create added value for property owners, tenants, and related business actors.